De la licéité du Mawlid - Nejmeddine Khalfallah (Revue des Mondes Musulmans et de la Méditerranée)
In this article, I will first analyse the argument that Tunisian scholar Muḥammad al-Ṭāhir b. ‘Āshūr (1879-1973) mobilised to justify the commemoration of the Mawlid. Faced with the silence of the scriptural sources, the Qur’an and the Sunnah, b. ‘Āshūr endeavoured to demonstrate the lawfulness of this commemoration by interpreting certain verses, on the one hand, and by endorsing the jurisprudential opinions (fatwā-s) of his predecessors, on the other hand, to finally deduce that celebrating the Mawlid is a “good way” (maslak hasan). In the second part, I discuss the political dimension of this demonstration in relation to beylical power in Tunisia since the eighteenth century.